2020
DOI: 10.1039/c9sc05544d
|View full text |Cite
|
Sign up to set email alerts
|

Design of a core–shell catalyst: an effective strategy for suppressing side reactions in syngas for direct selective conversion to light olefins

Abstract: The preparation of a Zn–Cr@SAPO capsule catalyst and the two different mass transfer routes over the capsule catalyst and physical mixture catalyst in light olefins synthesis from syngas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 61 publications
3
65
0
Order By: Relevance
“…As reported previous, H 2 adsorption positions were at the exposed lattice oxygen sites during the methanol synthesis reaction. These adsorbed H 2 can continuously convert into CH 3 O and finally CH 3 OH by attaching to the adjacent CO 2 donor [27] . For Cu‐ZnO samples, the lattice oxygen was believed to be responsible for the electoral transfer between ZnO and Cu nanoparticles, which was correlated with the content of Cu‐ZnO interface sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previous, H 2 adsorption positions were at the exposed lattice oxygen sites during the methanol synthesis reaction. These adsorbed H 2 can continuously convert into CH 3 O and finally CH 3 OH by attaching to the adjacent CO 2 donor [27] . For Cu‐ZnO samples, the lattice oxygen was believed to be responsible for the electoral transfer between ZnO and Cu nanoparticles, which was correlated with the content of Cu‐ZnO interface sites.…”
Section: Resultsmentioning
confidence: 99%
“…These adsorbed H 2 can continuously convert into CH 3 O and finally CH 3 OH by attaching to the adjacent CO 2 donor. [27] For Cu-ZnO samples, the lattice oxygen was believed to be responsible for the electoral transfer between ZnO and Cu nanoparticles, which was correlated with the content of Cu-ZnO interface sites. The author concluded that the increase of the content of lattice oxygen sites can increase the main active sites.…”
Section: Xpsmentioning
confidence: 99%
“…XRF result also demonstrated that the contents of Zn and Cr in oxide agree with the theoretical calculated value, as shown in Table S9 (Supporting Information). In the process of CO 2 to methanol, the oxygen vacancy plays an important role in adsorption and transformation of CO 2 [15] . As shown by Figure S4a, b and Table S10 (Supporting Information), after pretreatment by H 2 at 400 °C for 2 h, the concentrations of OH and O defect on the surface of ZnCr 2 O 4 were increased from 3 to 14 % and 21 to 28 %, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…CO was activated over the metal oxide, and C–C coupling proceeded over the acid sites in the zeolite. Several kinds of metal oxides have been utilized in the bifunctional catalysts, such as ZnCrO x , 3 7 ZrO 2 –ZnO, 8 ZnAlO x , 9 ZnO, 10 MnO x , 11 and Zr–In 2 O 3 . 12 SAPO-34, a silicoaluminophosphate zeotype with a chabazite (CHA) structure, 13 is the most popular zeotype used in the bifunctional catalyst for the STO process 4 , 5 , 8 12 and responsible for its excellent performance in the methanol-to-olefins (MTO) process.…”
Section: Introductionmentioning
confidence: 99%